The Role of the Phylogenetic Diversity Measure, PD, in Bio-Informatics: Getting the Definition Right - Daniel P. Faith (Evolutionary Bioinformatics, 2006)
A recent paper in this journal (Faith and Baker, 2006) described bio-informatics challenges in the application of the PD (phylogenetic diversity) measure of Faith (1992a), and highlighted the use of the root of the phylogenetic tree, as implied by the original definition of PD. A response paper (Crozier et al. 2006) stated that 1) the (Faith, 1992a) PD definition did not include the use of the root of the tree, and 2) Moritz and Faith (1998) changed the PD definition to include the root. Both characterizations are here refuted. Examples from Faith (1992a, b) document the link from the definition to the use of the root of the overall tree, and a survey of papers over the past 15 years by Faith and colleagues demonstrate that the stated PD definition has remained the same as that in the original 1992 study. PD's estimation of biodiversity at the level of “feature diversity” is seen to have provided the original rationale for the measure's consideration of the root of the phylogenetic tree.